Analisis Efektivitas Mesin Packer BG-04 dengan Metode Overall Equipment Effectiveness di Industri Pengolahan Tepung Terigu - Pratama, Cindy Novalia Dwi; Yuliawati, Evi; Sulistiarini, Emma Budi (Politeknik ATI Padang, 2023)
The wheat flour processing industry is a food industry in the form of production of wheat flour needs which has the main raw material in the form of wheat. The increasing demand and increasing competition in the wheat flour industry require the company to maintain its effectiveness level, one of which is machine effectiveness. One example of a machine at a wheat flour processing industry is the BG-04 packer machine. This study aims to analyze the causes of the non-achievement of the effectiveness of the BG-04 Packer machine which is indicated by the Overall Equipment Effectiveness value standard of 85% and the calculation of its constituent elements, namely Availability, Performance, and Quality. The results showed that the Overall Equipment Effectiveness value of the BG-04 Packer Machine was 60%, meaning that it is still far from effective. From the results of the analysis of six big losses and pareto diagrams show the cause of the low ineffectiveness iddling and minor stopages losses caused by machine stops in a short duration but often occurs. Therefore, it is necessary to make improvements through the results of the 5W+1H analysis, namely conducting training on understanding the machine and how to fix it, making the ergonomic chair of the packer operator, making a rubber backer replacement schedule outside production hours, making and applying SOP, processing distribution scheduling with the most optimal method of cleaning the machine before use.